Interest in Savings and Loan Cooperative Financing Products and Sharia Financing on Various Variables - Umi Hani’in; Harun Santosa (International Journal of Seocology, 2022)
The purpose of this study was to determine the effect of services, financing products, and customer perceptions of interest in financing products for the Sharia Savings and Loans Cooperative (KSPPS) BMT Samara. This research will be carried out using explanatory research, researchers conduct surveys and go to the research site by giving questionnaires to KSPPS BMT Samara financing customers directly. This study uses quantitative methods, where this method is used to test hypotheses. The population of this research is KSPPS BMT Samara financing customers, totaling 1,214 as of December 31, 2021. The sampling technique uses quota sampling technique, with a total sample of 100 financing customers. The data collection methods used in this study were the observation method, the documentation method, and the questionnaire method. The data analysis technique used is multiple regression analysis, t test, F test, and R2 test. The results of the study indicate that there is an effect of partial service on customer interest in financing products. There is no influence between financing products partially on customer interest in financing products. There is a partial influence between customer perceptions of customer interest in financing products. There is a simultaneous and joint influence of services, financing products and customer perceptions of customer interest in financing products and the simultaneous and joint influence of services and perceptions of interest in financing products is 42.1% and the rest is influenced by other variables undetermined.